THE EFFECT OF EXECUTIVE CHARACTERISTICS, CONSTITUTIONAL OWNERSHIP, PROFITABILITY, AND LEVERAGE ON TAX AVOIDANCE IN COAL SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2020 PERIOD - Melita Yuniza; Sucipto; Agustina Mutia (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to determine the influence of executive, constitutional ownership, profitability, and leverage against tax avoidance in the enterprise sub-sector coal, which memiliki owns shares sharia listed on the Indonesia Stock Exchange. The sampling technique in this study used purposive sampling. 11 coal sub-sector companies were sampled in the study during the 2015-2020 period. This research is a quantitative study using secondary data. The analysis technique in this research is panel data analysis. The results of this study indicate that the characteristics of the Executive, Constitutional Ownership, and Return on Assets affect Tax Avoidance. At the same time, the Debt to Equity Ratio does not affect Tax Avoidance.